STUDI KOMPARATIF USAHATANI SEMANGKA NON-BIJI PADA KELOMPOK TANI RIDHO LESTARI DI KABUPATEN BANYUWANGI - Rizki Dedi; Lenny Widjayanthi; Sudarko Sudarko (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Ridho Lestari farmer group are non-seed watermelon farmer groups who have permanent members and non-permanent members. Permanent members are farmers who have land while non permanent members are the farmers who do not have their own land. They rent from other farmers. This study aims to determine income, cost eficiency, and factors that influence farmer’s income. The study was conducted in the village of the district Muncar Tembokrejo districts Banyuwangi used analytical and comparative method. Sampling method used total sampling as much as 50 respondents. The data collection using interviews and literature were analyzed by income analysis, R/C ratio, and multiple linear regression. The results shows that (1) There were differences income significantly between permanent members and non-permanent members (2) There were differences on cost efficiency significantly between permanent members and non-permanent members (3) Factors that significantly influence farmer’s income were field cost (Rp), seed cost (Rp), pesticide cost (Rp), labor cost (Rp), sales volume (kg) and the selling price (Rp/Kg)